Mesenchymal stem cells are sensitive to bleomycin treatment - Nicolay, Nils; Rühle, Alexander; Trinh, Thuy; Sisombath, Sonevisay; Weber, Klaus-Josef; Ho, Anthony Dick; Debus, Jürgen; Saffrich, Rainer; Huber, Peter E. (Scientific reports, 2016)
Mesenchymal stem cells (MSCs) have been shown to attenuate pulmonary damage induced by bleomycin-based anticancer treatments, but the influence of bleomycin on the stem cells themselves remains largely unknown. Here, we demonstrate that human bone marrow-derived MSCs are relatively sensitive to bleomycin exposure compared to adult fibroblasts. MSCs revealed increased levels of apoptosis after bleomycin treatment, while cellular morphology, stem cell surface marker expression and the ability for adhesion and migration remained unchanged. Bleomycin treatment also resulted in a reduced adipogenic differentiation potential of these stem cells. MSCs were found to efficiently repair DNA double strand breaks induced by bleomycin, mostly through non-homologous end joining repair. Low mRNA and protein expression levels of the inactivating enzyme bleomycin hydrolase were detected in MSCs that may contribute to the observed bleomycin-sensitive phenotype of these cells. The sensitivity of MSCs against bleomycin needs to be taken into consideration for ongoing and future treatment protocols investigating these stem cells as a potential treatment option for bleomycin-induced pulmonary damage in the clinic.
Gesehen am 09.09.2019